Simulasi Layanan dan Antrian Pencucian Mobil Berbasis Web pada R&D Premium Wash - Rotisno, R.Ryan Rizky (JURNAL TEKNIK INFORMATIKA, 2023)
Abstract— R&D Premium Wash Kupang is one of the service companies that provides services in the form of a car wash that has 1 washing place and is equipped with 2 hydraulic facilities. The problem at the company is the occurrence of queues that result in losses of time and energy, these problems affect the company's revenue and the quality of the company's performance when customers are reluctant to wait and choose another car wash, so it is important for the company to implement a queuing model that can provide waiting time information. Queues occur also due to the absence of an online booking process to provide additional services for customers so that customers do not have to wait at the wash. The solution provided is to apply the Jeckson Network Queue Method with First-In First-Out (FIFO) queuing discipline. The test results using the confusion matrix, got an accuracy rate of 95% silver, 97% gold, 98% platinum, and 96% emerald. The precision level of silver is 80%, gold 88%, platinum 92% and emerald 84%. The sensitivity level is 100% in all classes and the f1-score level of silver is 88%, gold 93%, platinum 95% and emerald 91%. Keywords—Booking, First-In First-Out (FIFO), Jeckson Network Queue, matrix confussion, Queuing System, Service, R&D Premium Wash Kupang.